IMPLEMENTASI COLLABORATIVE ROBOTS ARTIFICIAL INTELLIGENCE PADA OTOMATISASI INSPEKSI KENDARAAN UNTUK MENINGKATKAN KINERJA - I Kadek Agus Hendriawan Putra, I Wayan Bandem Adnyana, Desak Ayu Sista Dewi, Anak Agung Istri Agung (Study Program of Industrial Engineering, Udayana University, 2023)
High competition in the automotive industry requires companies to innovate in order to compete and increase productivity. The Toyota Production System method is a method that can be used to increase work productivity, especially in eliminating waste. There are several processes in the automotive industry, one of which is quality control, which checks and ensures that the goods received by consumers do not have zero defects. During the quality control process, there was work that was not ergonomic which was assessed using the rapid entire body assessment method and received a high score which ergonomically can cause musculoskeletal disorders (MSDs), so improvements need to be made, namely in POS FWA Lower. In this study, collaborative robots are used along with payload cameras and artificial intelligence to replace human work so that work can be eliminated. Apart from that, in this POS, there is an idle time of 45 seconds because there is a working machine, but if use collaborative robots, this idle time can be eliminated to increase productivity. The results show that implementing cobot AI can significantly increase productivity and efficiency in the quality control process by increasing total work time performance by 1.76 times, Reba score performance by 11 times, and idle time performance by 45 times, as well as the accuracy of the AI model gets an accuracy value of 99.1%.